2020
DOI: 10.1007/s00213-020-05596-8
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine intake and cognitive functions in children

Abstract: Rationale-There is a growing concern over excessive caffeine use and development of caffeine use disorder in children.Objectives-This study aimed to identify the association between caffeine intake and cognitive functioning in children.Methods-This study included 11718 youths aged 9-10 years with cognitive and caffeine intake information that were extracted from the Adolescent Brain Cognitive Development (ABCD) Study. The ABCD study is a longitudinal cohort study started in 2017 that aims to understand the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…The ABCD study is longitudinal but only cross-sectional research was reported by Zhang, Lee and Qiu (2020). Other cross-sectional research does initially support the results of Zhang, Lee and Qiu (2020) and extends them to other sources of caffeine, age groups and outcomes.…”
Section: The Design Of the Abcd Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The ABCD study is longitudinal but only cross-sectional research was reported by Zhang, Lee and Qiu (2020). Other cross-sectional research does initially support the results of Zhang, Lee and Qiu (2020) and extends them to other sources of caffeine, age groups and outcomes.…”
Section: The Design Of the Abcd Studymentioning
confidence: 99%
“…The ABCD study is longitudinal but only cross-sectional research was reported by Zhang, Lee and Qiu (2020). Other cross-sectional research does initially support the results of Zhang, Lee and Qiu (2020) and extends them to other sources of caffeine, age groups and outcomes. Smith and Richards (2018) examined associations between energy drink consumption and academic attainment of secondary school pupils.…”
Section: The Design Of the Abcd Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies have shown positive associations between caffeine consumption and memory, two most recent studies have shown data demonstrating a negative association. Zhang et al, performed a population-based study which analyzed data from an ongoing Adolescent Brain Cognitive Development (ABCD) study to assess the effects of caffeine on cognitive function in children [ 20 ]. A total of 11,875 participants, aged 9-10, consisting of a similar proportion of males and females living in the United States were recruited [ 27 ].…”
Section: Reviewmentioning
confidence: 99%
“…According to the USDA National Nutrient Database, this average equates to approximately one-eighth of a can (12 fl oz) of AMP energy drink or two packs of M&M’s Milk Chocolate candy. In contrast to popular belief, Zhang et al suggested that caffeine consumption had a negative correlation with working memory, episodic memory, and processing speed (p < 0.01), suggesting that children who chronically consumed caffeine exhibited a worsening in overall cognitive performance [ 20 ]. This may indicate that habitual caffeine consumption could have detrimental effects on neurologic development in children, especially during critical neurological developmental periods.…”
Section: Reviewmentioning
confidence: 99%